Cytotoxic and apoptotic effects of chalcone derivatives of 2‐acetyl thiophene on human colon adenocarcinoma cells. (18th September 2012) - de Vasconcelos, Alana; Campos, Vinicius Farias; Nedel, Fernanda; Seixas, Fabiana Kömmling; Dellagostin, Odir A.; Smith, Kevin R.; de Pereira, Cláudio Martin Pereira; Stefanello, Francieli Moro; Collares, Tiago; Barschak, Alethéa Gatto
Abstract : Recent studies report that chalcones exhibit cytotoxicity to human cancer cell lines. Typically, the form of cell death induced by these compounds is apoptosis. In the context of the discovery of new anticancer agents and in light of the antitumour potential of several chalcone derivatives, in the present study, we synthesized and tested the cytotoxicity of six chalcone derivatives on human colon adenocarcinoma cells. Six derivatives of 3‐phenyl‐1‐(thiophen‐2‐yl) prop‐2‐en‐1‐one were prepared and characterized on the basis of their 1 H and 13 C NMR spectra. HT‐29 cells were treated with synthesized chalcones on two concentrations by three different incubation times. Cells were evaluated by cell morphology, Tetrazolium dye (MTT) colorimetric assay, live/dead, flow cytometry (annexin V) and gene expression analyses to determine the cytotoxic way. Chalcones 3‐(4‐bromophenyl)‐1‐(thiophen‐2‐yl)prop‐2‐en‐1‐one (C06) and 3‐(2‐nitrophenyl)‐1‐(thiophen‐2‐yl)prop‐2‐en‐1‐one (C09) demonstrated higher cytotoxicity than other chalcones as shown by cell morphology, live/dead and MTT assays. In addition, C06 induced apoptosis on flow cytometry annexin V assay. These data were confirmed by a decreased expression of anti‐apoptotic genes and increased pro‐apoptotic genes. Our findings indicate in summary that the cytotoxic activity of chalcone C06 on colorectal carcinoma cells occurs by apoptosis. Copyright © 2012 John Wiley & Sons, Ltd.